Axenfeld-Rieger syndrome – A report of a rare case and review - Senthilkumar, Eyakshara; Manoharan, Murali Gopika (Indian Journal of Case Reports, 2024)
A typical case of Axenfeld-Rieger syndrome (ARS), a rare autosomal dominant condition manifesting with ocular, craniofacial, and dental abnormalities, is presented. The patient showed dental features such as oligodontia, microdontia, abnormally shaped teeth, hyperplastic maxillary labial frenum, and maxillary retrognathism. Early diagnosis of the syndrome from its dentofacial manifestations and a multidisciplinary approach is required for the management of patients with ARS.